Reversible pH Responsive Bovine Serum Albumin Hydrogel Sponge Nanolayer - Raghuwanshi, Vikram Singh; Yu, Brendan; Browne, Christine; Garnier, Gil (Frontiers in Bioengineering and Biotechnology, 2020)
A pH dependent reversible sponge like behaviour of a BSA nanolayer adsorbed at the gold-saline interface is revealed by QCM-D, AFM and contact angle measurements. During the saline rinsing cycles, the BSA layer adsorbs water molecules at pH 7.0 and releases them at pH 4.5. The phenomenon remains constant and reproducible upon multiple rinsing cycles. The BSA layer thickness also increases upon rinsing with saline at pH 7.0 and reverses back to its original thickness at pH 4.5. Varying ionic strength with water further desorbs more water molecules from the BSA layer, which decreases its mass and thickness. However, upon both pH and ionic strength changes, all the BSA molecules remain adsorbed irreversibly at the gold interface and only the sorption of water molecules occurs. The study aims at engineering high efficiency pH-responsive biodiagnostics and drug delivery systems.